The use of mathematical methods for decision making in optimal pricing strategy for enterprises - Shevchenko, N.; Gudkova, E. (Економічний вісник Донбасу, 2016)
It is noted that the development, modification and adaptation of methods and pricing models takes place according to the conditions in which the price is formed. It is indicated that the variability of the external conditions of functioning of enterprises (political and economic) determines the relevance of the issue of choosing the optimal pricing strategy under uncertainty and risk. The task of developing a model of the optimal pring strategy of industrial enterprise in the conditions of uncertainty and risk of the generated sets of strategies. It is indicated that the choice of the enterprise will depend on the projected sales volume for the next period and the ratio of the company's management to the economic risk. This situation is presented in the form of a statistical game where players act on the one hand the company's management, and on the other - the level of demand (the planned volume of sales) in the company's products. Choosing the optimal strategy is proposed to carry out with the help of decision criteria: Bayes, Wald and Laplace. Відмічено, що розвиток, модифікація і адаптація методів і моделей ціноутворення відбувається з урахуванням умов, в яких формується ціна. Зазначено, що мінливість зовнішніх умов функціонування підприємств (політичних і економічних) визначає актуальність питання вибору оптимальної цінової стратегії в умовах невизначеності і ризику. Поставлено завдання розробки моделі формування оптимальної цінової стратегії виробничого підприємства в умовах невизначеності і ризику із сформо- ваної множини стратегій. Наголошено, що вибір підприємства залежатиме від прогнозованого об'єму реалізації на майбутній період і відношення керівництва підприємства до економічного ризику. Вкаана ситуація представлена у вигляді статистичної гри, де гравцями виступають з одного боку керівництво підприємства, а з іншого - рівень попиту (планований об'єм реалізації) на продукцію підприємства. Вибір оптимальної стратегії пропонується здійснювати за допомогою критеріїв прийняття рішень: Байєса, Вальда і Лапласа. Отмечено, что развитие, модификация и адаптация методов и моделей ценообразования происходит с учетом условий, в которых формируется цена. Указано, что изменчивость внешних условий функционирования предприятий (политических и экономических) определяет актуальность вопроса выбора оптимальной ценовой стратегии в условиях неопределенности и риска. Поставлена задача разработки модели формирования оптимальной ценовой стратегии производственного предприятия в условиях неопределенности и риска из сформированного множества стратегий. Отмечено, что выбор предприятия будет зависеть от прогнозируемого объема реализации на будущий период и от отношения руководства предприятия к экономическому риску. Указанная ситуация представлена в виде статистической игры, где игроками выступают с одной стороны руководство предприятия, а с другой - уровень спроса (планируемый объем реализации) на продукцию предприятия. Выбор оптимальной стратегии предлагается осуществлять с помощью критериев принятия решений: Байеса, Вальда и Лапласа.